Die antitese tussen witboordjiemisdaad en sake-etiek - Lotriet, R. A. (2007)
The antithesis between white-collar crime and business ethics Transparency International states that the scourge of whitecollar crime and corruption is endemic in both the developed and developing world. South Africa is no exception, as the perception prevails that not only have violent crimes increased in recent years, but that white-collar crimes are also escalating. Very little academic research on white-collar crime has been undertaken thus far. Like the Postmodern Movement, the current technology-driven network economy has no foundational ethic, which creates the ideal situation for further fostering the seeming lack of shared values. But there is no reason to accept the imperative of the new order without challenge. Therefore, ethics education at management level has a fundamental role to play in the market operations of the 21st century. The article explores what is happening in practice at business school level and their focus worldwide on relevant training to address the needs of the dynamic market environment.
Keywords: White-collar Crime; Business Schools; Business Ethics